2020
DOI: 10.1111/ijac.13451
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of sol gel derived nontoxic CZTS thin films without sulfurization

Abstract: Recently, great attention has been paid to the development of earth rich and nonhazardous Copper Zinc Tin Sulfide (CZTS-Cu 2 ZnSnS 4 ) thin films for application in photovoltaic devices owing to its high absorption coefficient over the visible and infrared region. However, sulfurization process is an indispensable step in growing stoichiometric thin film using conventional physical vapor deposition. Hence, it is imperative to devise a liquid based technique without intentional sulfurization for the optimum qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Sulfurization is crucial in CZTS preparation since the conventional sulfurization methods involve use of toxic chemicals and could cause formation of S-based impurities that could hinder the photovoltaic performance of CZTS-based solar cells. [4,[6][7][8][9][16][17][18][19]28] In this context, the present work investigates a straightforward sulfurization procedure, in which electrodeposition is combined with a solution process. At first, the CZT layers were prepared by sequential electrodeposition of Cu, Zn, and Sn at a current density of 0.01 A/cm 2 in the S1, S2, and S3 solutions that detailed in the experimental section (Table 7), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sulfurization is crucial in CZTS preparation since the conventional sulfurization methods involve use of toxic chemicals and could cause formation of S-based impurities that could hinder the photovoltaic performance of CZTS-based solar cells. [4,[6][7][8][9][16][17][18][19]28] In this context, the present work investigates a straightforward sulfurization procedure, in which electrodeposition is combined with a solution process. At first, the CZT layers were prepared by sequential electrodeposition of Cu, Zn, and Sn at a current density of 0.01 A/cm 2 in the S1, S2, and S3 solutions that detailed in the experimental section (Table 7), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Sputtering directly from CZTS alloy targets or co-sputtering methods do not provide the necessary stoichiometry as sulfur remains deficient in vacuum atmosphere due to its high saturation vapor pressure. [4][5][6] Besides, the sputtering rates of different elements are naturally not equal, and secondary phases can nucleate to act as recombination centers, degrading the solar cell performance. [5] In fact, sulfurization is highly influential regarding the resultant performance since the main drawback of CZTS is related to the presence of S-based impurities such as Cu 2 S, Cu 2 SnS 3 , ZnS, and SnS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 1 ] In fact, the bandgap of CZTS matches well with the theoretically predicted ideal bandgap of a semiconductor which can absorb a good part of the solar spectrum and produces good solar cell outputs. [ 2 ] On the other hand, CZTS material has an additional advantage because it can be prepared by several methods such as sputtering, [ 3,4 ] thermal evaporation, [ 5,6 ] spray pyrolysis, [ 7,8 ] sol–gel technique, [ 9,10 ] and electrodeposition. [ 11,12 ] In the literature, it has been reported that PV devices fabricated with CZTS films prepared with different techniques demonstrate the efficiency dependence on growth techniques.…”
Section: Introductionmentioning
confidence: 99%